Diabetic Foot Management: A Review of Current Knowledge - Kaweewan, Rungrujee; Arworn, Supapong; Kosachunhanun, Natapong; Sony, Kiran; Inpankaew, Nimit; Rerkasem, Kittipan (The Thai Journal of Surgery, 2016)
In recent years, Diabetes Mellitus (DM) has become more common. This issue will become critical throughout Asia, including Thailand, because the prevalence increase in type 2 DM shows no sign of reaching a plateau. As is well known, the most common cause of leg amputation in non-traumatic patients is DM foot. This is because DM patients have neuropathy, angiopathy, and immunopathy. The aim of the present review is to briefly update information on DM foot management, in particular on ulcer prevention, foot infection management, off-loading technique, footwear, revascularization, and prognosis. At the end of this review, we report our research on the strikingly poor prognosis of Asian DM patients with peripheral arterial disease observed during a six-month period.